Tiroglossal Kanal Kistinde İnce İğne Aspirasyon Biopsisi İle Tanımlanan Papiller Karsinom - Kılıç, Mehmet; Yoldaş, Ömer; Ertan, Tamer; Göçmen, Erdal; Koç, Mahmut (Fırat University, 2005)
Tiroglossal kanal kistinde malign lezyon gelişimi oldukça nadirdir. Malignite eksize edilen cerrahi spesimenin histolojik incelemesinde tesadüfen saptanır. Tiroglossal kanal kistinde ince iğne aspirasyon biyopsisi ile papiller karsinomun tanımlandığı bir olgu sunuyoruz.©2005, Fırat Üniversitesi, Tıp Fakültesi

The malignant lesion from of Thyroglossal Duct Cyst is extremely rare. The diagnosis of malignancy was made incidentally on hystologic study of the excised surgical specimen. We described a case of Thyroglossal Duct Cyst in which fine needle aspiration cytological study established presence of papillary carcinoma ©2005, Fırat Üniversitesi, Tıp Fakültesi
Papillary Carcinoma of Thyroglossal Canal Cyst Detected by Fine Needle Aspiration Cytology